18F-FDG and 68Ga-FAPI-04 PET/CT Imaging of a Case With Immunoglobulin G4–Related Disease Presenting as Hepatic Masses. (9th December 2022) - Zhang, Zeyu; Jiang, Hui; Zhang, Lu; Cheng, Chao; Zuo, Changjing
Abstract: Two hepatic masses were discovered through ultrasonography in a 50-year-old man with increased CA19-9, which is highly suspicious for malignancy. PET/CT images revealed intense 18 F-FDG and 68 Ga-FAPI-04 uptake in intrahepatic lesions. Histopathology with biopsy confirmed the diagnosis of immunoglobulin G4 (IgG4)–related disease. Here, we reported a case of IgG4-related primary localized pseudotumor without any other organ involvement. We concluded that in clinical work, if intrahepatic masses show high uptake of 18 F-FDG or 68 Ga-FAPI-04, intrahepatic IgG4-related disease should be considered for differential diagnosis.